2022
DOI: 10.3389/fmars.2022.855009
|View full text |Cite
|
Sign up to set email alerts
|

Competitive Interactions Between Microbial Siderophores and Humic-Like Binding Sites in European Shelf Sea Waters

Abstract: Siderophores are low molecular weight high affinity iron chelates found at low concentrations in seawater. In this study we determined the total concentrations and identities of siderophores in extracts isolated from a shelf sea environment on the Northwest European shelf by high performance liquid chromatography coupled to high resolution inductively coupled plasma mass spectrometry (ICP-MS) in parallel to high resolution electrospray ionisation mass spectrometry (ESI-MS). We identified a total of 24 differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 67 publications
1
5
0
Order By: Relevance
“…The remaining 3 nmol eq-Fe L -1 of the L Fe pool may be considered as weaker ligands compared to L FeHS . Our findings are consistent with the results reported by Gledhill et al, 2022, who demonstrated that the heterogeneity of binding sites in humic-like DOM enables humic substances to outcompete siderophores at low iron concentrations.…”
Section: Classification Of L Fehs and Iron Speciation Within L Fehs I...supporting
confidence: 93%
See 1 more Smart Citation
“…The remaining 3 nmol eq-Fe L -1 of the L Fe pool may be considered as weaker ligands compared to L FeHS . Our findings are consistent with the results reported by Gledhill et al, 2022, who demonstrated that the heterogeneity of binding sites in humic-like DOM enables humic substances to outcompete siderophores at low iron concentrations.…”
Section: Classification Of L Fehs and Iron Speciation Within L Fehs I...supporting
confidence: 93%
“…In regard to CLE-CSV data, L FeHS are mainly assigned to the intermediate class of ligand (e.g. L 2 ; Laglera and van den Berg, 2009;Gledhill and Buck, 2012) but this complex mixture possibly includes components of other classes (Perdue and Lytle, 1983;Laglera et al, 2019;Gledhill et al, 2022). Field observations (Buck et al, 2018) and numerical simulations (Misumi et al, 2013) suggest that L 2 type ligands regulate the DFe distribution as well as its residence time in the deep ocean (Hunter and Boyd, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Concentrations of Fe SPE-amb in the marine end-member (0.12 ± 0.03 nM) were an order of magnitude higher than the highest siderophore concentrations reported in the ocean ( 44 ). We further highlight that recoveries of siderophores are typically higher [46%; ( 44 )] than the average recovery observed for DOC in this study, and siderophores may therefore make up a minor component of the total organically bound Fe fraction in coastal waters ( 45 ).…”
Section: Resultsmentioning
confidence: 57%
“…Such models provide an estimation of metal speciation (Hiemstra and van Riemsdijk, 2006;Stockdale et al, 2011) linking DOM bioavailability with iron solubility (Zhu et al, 2021a). These models may be appropriate in the marine setting given recognition that much of the complexation capacity in the ocean may be attributed to polydisperse degradation products and, in accounting for the complexity of seawater DOM, the NICA-Donnan model approach may better predict iron bioavailability in natural waters (Zhu et al, 2021a;Gledhill et al, 2022aGledhill et al, , 2022b. However, there are still open questions regarding the extent to which speciation is well described by assumptions of thermodynamic equilibrium and the extent to which different metals may compete for the same metal binding sites.…”
Section: Modeling Metal Speciation and Cyclingmentioning
confidence: 99%